The utilization of Intergrowth-21st Growth Curves for Preterm Newborns in a Brazilian Neonatal Intensive Care Unit in southern Brazil (Research, Society and Development, 2021)
Use the postnatal growth curves of the INTERGROWTH-21st project for preterm newborns admitted to the Neonatal Intensive Care Unit of the Teaching Hospital of the Federal University of Pelotas-RS. Seventy newborns were followed up, with a prospective longitudinal design, from birth and / or hospitalization to discharge or death from the neonatal intensive care unit, from October 2018 to April 2019. Age estimated gestational age ranged from 19 to 36 weeks (mean 31 weeks), and 40% of newborns had birth weight less than 1500 g, with 89% weighing less than 2500 g. Sixty preterm newborns were discharged and ten died during hospitalization - neonatal mortality of 143 per 10,000 live births. About 60% of births occurred by cesarean section, and 13% of newborns had an Apgar score below 4 in the first minute of life. It was observed that through anthropometric measurements, both in boys and girls, during hospitalization, they were mostly within the normal limits of growth, and the growth percentiles of children who were born and were followed from birth until two weeks or more of hospitalization had an increase in weight and length, about 37.1% and 51.4%, respectively. It appears that the growth of preterm newborns was satisfactory and that the use of the Intergrowth growth patterns, through their post-natal anthropometric curves, are useful and easy to apply in the daily routine of the unit neonatal intensive care.